‘Mais Médicos’ e as residências municipais de medicina de família e comunidade: fortalecendo a formação para o SUS ou alguns tropeços no caminho? - Paes, Mariana Fonseca [UNIFESP] (2019)
Introduction: This research focused on education and training within the program “More Doctors for Brazil”, concentrating on initiatives taken by the Ministry of Health and Ministry of Education from 2013 to 2015, which were designed to stimulate the expansion of the Family and Community Medicine Residency. Objectives: This research sought to: describe municipal experiences in implementing medical residency programs and the partnerships established between municipalities and the Ministry of Health to enable implementation, and identify the perception of former residents and coordinators within the municipal programs about the formation process and the resulting impact on the municipalities. Methodology: This study was conducted in a qualitative and exploratory nature, through documentary research and open interviews with actors involved—including the first graduates of the program—about the process of implementation of the medical residency programs in three municipalities in the state of São Paulo. For the analysis of the material, narratives were produced by the researcher from the interview transcripts, which were then mined for the identification of emerging issues. Results and Discussion: From the subjects addressed it was possible to identify the importance of federal financial incentives for program implementation and local support, but fears exist about the continuity of the programs in the face of federal and municipal political changes. In the three municipalities contemplated, there was a reconfiguration in the coordination of permanent education programs and the residency programs were linked to those changes; this restructuring strengthened teaching-service integration. The inclusion of medical specialties, which don’t exist within the municipal healthcare system, was found to be particularly challenging. Including specialties within the residency rotation depended on the willingness of the physicians of each specialty to participate as preceptors, which required partnerships with specialized outpatient clinics at medical schools. The role of the preceptor was considered essential in solidifying the link between resident and the program and the pedagogical preparation of preceptors, which historically had been lacking, was understood to be fundamental. Balancing the dual needs of patient care with resident education within the residency created conflicts, and demonstrated that even in residency it was necessary to deal with the real demands of the public healthcare centers. Family medicine, in comparison, appeared to offer greater flexibility because of its more routine nature, and provided greater financial incentives after training, giving priority to continue working in the HUS. Final considerations: The study points out advances in the variety of professional training strategies for and within HUS; however, it is not possible to declare that municipal residency programs have generated contributions to a more multi-professional and less doctor centered education. The specific clinical practice of family medicine seemed not to dialog with other health professions, and perhaps this could be considered one of the essential stumbling blocks.